Algoritma Fast Corner Detection dan Natural Feature Tracking Media Tumbuhan Berbasis Augmented Reality - aldy febriyandani (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Technological advances today are very rapid, one of which is in the field of learning media or education. Augmented Reality (AR) Technology is an amalgamation of digital content that has been created on a computer from the real world. This study aims to provide an introduction to plants so that they can find out information about the plant. This study uses a method, namely natural feature tracking and uses a development system, namely MDLC (Multimedia Development Life Cycle) and uses Fast Corner Detection and Natural Feature Tracking algorithms, resulting in an application that can display 3D objects about plants, and there is a brief explanation of plants, This application can use the Android operating system, Testing the application using 3 android phones, namely Samsung A2018 with android version 9, Oppo A9 2019 and Samsung A51 2020 that when the slope is <18 ° the three cellphones do not detect the marker while at an angle of 20 ° -60° and 61°-90° the three mobile phones can detect and be read on the mobile screen.